A Holistic AI-Enabled Enterprise Transformation Framework Integrating Generative AI Cloud-Native Infrastructure MLOps Cybersecurity and Predictive Automation (International Journal of Research Publications in Engineering, Technology and Management (IJRPETM), 2026)
The emergence of artificial intelligence, cloud-native technologies, predictive analytics, and intelligent automation has fundamentally transformed the way enterprises operate, innovate, and compete in the digital economy. Organizations increasingly seek integrated frameworks that combine Generative Artificial Intelligence (GenAI), cloud-native infrastructure, Machine Learning Operations (MLOps), cybersecurity, and predictive automation to achieve sustainable digital transformation. However, the implementation of these technologies in isolation often leads to fragmented systems, governance challenges, security vulnerabilities, and reduced operational effectiveness. This study proposes a holistic AI-enabled enterprise transformation framework that unifies these critical technological domains within a cohesive architecture. The framework leverages cloud-native scalability, automated machine learning lifecycle management, AI-driven security intelligence, and predictive decision-making capabilities to enhance organizational agility, resilience, and efficiency. By integrating Generative AI into enterprise workflows, organizations can improve knowledge management, customer engagement, software development, and business process optimization. Simultaneously, MLOps practices ensure reliable deployment and monitoring of machine learning models, while cybersecurity mechanisms safeguard digital assets against evolving threats. Predictive automation further enhances operational performance through intelligent forecasting and autonomous process execution. The proposed framework provides a comprehensive approach to enterprise modernization, enabling organizations to maximize innovation, improve decision quality, strengthen security, and accelerate digital transformation in increasingly dynamic business environments.
Keywords: Artificial Intelligence; Generative AI; Enterprise Transformation; Cloud-Native Infrastructure; MLOps; Cybersecurity; Predictive Automation; Digital Transformation; Machine Learning; Intelligent Automation; Cloud Computing; Enterprise Architecture; AI Governance; Operational Intelligence; Business Innovation